Transferring ART research into education in Brazil - Maria Fidela de Lima Navarro; Karin Cristina da Silva Modena; Maria Cristina Carvalho de Almendra Freitas; Ticiane Cestari Fagundes (University of São Paulo, 2009)
The aim of this study was to evaluate the teaching of the Atraumatic Restorative Treatment (ART) approach in Brazilian dental schools. MATERIALS AND METHODS: A questionnaire on this subject was sent to Pediatric Dentistry, Operative Dentistry and Public Health Dentistry professors. The questions approached the followig subjects: the method used to teach ART, the time spent on its teaching, under which discipline it is taught, for how many years ART has been taught and its effect on the DMFT index. RESULTS: A total of 70 out of 202 dental schools returned the questionnaire. The ART approach is taught in the majority of the Brazilian dental schools (96.3%), and in most of these schools it is taught both in theory and in clinical practice (62.9%). The majority (35.3%) of professors teach ART for 8 hours, and most often as part of the Pediatric Dentistry discipline (67.6%). It has been taught for the last 7 to 10 years in 34.3% of dental schools. Most professors did not observe a change in the DMFT index with this approach. There is a diversity in the teaching of ART in Brazil in terms of the number of hours spent, the teaching method (theory and practice), and the disciplines involved in its teaching. CONCLUSIONS: It is necessary to address the training of professors in the ART approach for the whole country. An educational model is proposed whereby a standard ART module features as part of other preventive and restorative caries care educational modules. This will facilitate and standardize the introduction and adoption of the ART approach in undergraduate education in Brazil.